2010
DOI: 10.1614/ws-d-09-00011.1
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Movement of Synthetic Auxin Herbicides: Aminocyclopyrachlor, Aminocyclopyrachlor-Methyl Ester, Dicamba, and Aminopyralid

Abstract: Aminocyclopyrachlor, a newly discovered synthetic auxin herbicide, and its methyl ester, appear to control a number of perennial broadleaf weeds. The potential volatility of this new herbicide and its methyl ester were determined under laboratory conditions and were also compared to dicamba and aminopyralid with the use of enclosed chamber and open-air plant bioassays. Bioassays consisting of visual estimates of epinastic responses and kidney bean and soybean leaf-width measurements were developed to measure v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 7 publications
3
55
0
7
Order By: Relevance
“…According to Strachan et al (2010) these intoxication symptoms in Magnoliopsida species are similar to those observed when applying the herbicide aminopyralid, which also has the same mechamism of action. For beets, seedling emergence was verified, however, plants died even in the same soil with the lowest dose of aminocyclopyrachlor (10 g ha .…”
Section: F Lsupporting
confidence: 62%
See 2 more Smart Citations
“…According to Strachan et al (2010) these intoxication symptoms in Magnoliopsida species are similar to those observed when applying the herbicide aminopyralid, which also has the same mechamism of action. For beets, seedling emergence was verified, however, plants died even in the same soil with the lowest dose of aminocyclopyrachlor (10 g ha .…”
Section: F Lsupporting
confidence: 62%
“…Thus, the I 50 value of these crops was higher than the highest dose tested (> 50 g ha -1 ) ( Table 1). Strachan et al (2010Strachan et al ( , 2011) also tested the sensitivity of various species to aminocyclopyrachlor and found that none of the Liliopsida species were sensitive to this herbicide, so that even the soil application of 64 g ha -1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolerance was achieved through the insertion of bacterial genes into soybean that allows the plant to metabolize 2,4-D. [21]. Previous research has documented that up to 16% of spray solution can physically drift from the intended application area [22].…”
Section: Dow Agrosciencesmentioning
confidence: 99%
“…Dicamba is a growth regulator that mimics the endogenous plant hormone indole-3-acetic acid (IAA) and causes the over-proliferation of plant cells at the meristematic regions, leading to death [13]. Auxin-like growth regulating herbicides, such as dicamba, are susceptible to off-target movement due to volatilization and subsequent vapor drift [14]. Several different salt formulations of dicamba have been developed to minimize the off-target damage to sensitive broadleaf crops due to volatilization and vapor drift [12].…”
Section: Monsantomentioning
confidence: 99%